Impactful innovations. Lessons from family agriculture in Latin America and the Caribbean - Henríquez, Priscila (Insituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
This document summarizes the fifteen projects that were selected by a panel of international experts as those which best represent the technological, institutional and organizational innovations carried out with and by small farmers – known as family farming - in LAC. This is the result of a hemisphere-wide competition organized in 2012 by FONTAGRO, with the aim of (1) showcasing success stories in which innovations having positive economic, social, and environmental impacts have been implemented and, (2) raising awareness regarding the importance of investing in innovation. The cases selected document the many successes achieved by producers, processors or traders who, alone or with occasional support from the public sector and NGOs, are increasing productivity, reaching more demanding markets, adding value to their products and obtaining better prices.